2017
DOI: 10.1074/jbc.m116.762831
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a feedback loop involving β-glucosidase 2 and its product sphingosine sheds light on the molecular mechanisms in Gaucher disease

Abstract: The lysosomal acid β-glucosidase GBA1 and the non-lysosomal β-glucosidase GBA2 degrade glucosylceramide (GlcCer) to glucose and ceramide in different cellular compartments. Loss of GBA2 activity and the resulting accumulation of GlcCer results in male infertility, whereas mutations in the gene and loss of GBA1 activity cause the lipid-storage disorder Gaucher disease. However, the role of GBA2 in Gaucher disease pathology and its relationship to GBA1 is not well understood. Here, we report a GBA1-dependent dow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 36 publications
2
26
0
Order By: Relevance
“…However, some of these results have not been validated in subsequent studies, as Schonauer et al. found GBA2 to be downregulated or at control levels in the absence of GCase activity, and that sphingosine itself binds to GBA2 and inhibits the further formation of sphingosine (Schonauer et al., ). These conflicting results indicate that while GBA2 may play a role in GD pathogenesis, its exact role is unclear.…”
Section: Modifiers Of Gaucher Disease: Results Of Candidate Gene Studiesmentioning
confidence: 99%
“…However, some of these results have not been validated in subsequent studies, as Schonauer et al. found GBA2 to be downregulated or at control levels in the absence of GCase activity, and that sphingosine itself binds to GBA2 and inhibits the further formation of sphingosine (Schonauer et al., ). These conflicting results indicate that while GBA2 may play a role in GD pathogenesis, its exact role is unclear.…”
Section: Modifiers Of Gaucher Disease: Results Of Candidate Gene Studiesmentioning
confidence: 99%
“…In the context of Gaucher disease, a lysosomal storage disorder that develops due to loss of GBA1 activity, we have demonstrated that loss of GBA1 activity results in a concomitant reduction in GBA2 activity (24). However, vice versa, loss of GBA2 activity does not affect GBA1 activity (24).…”
Section: Gba2 Mutations and Locomotor Dysfunctionmentioning
confidence: 94%
“…Loss of GBA2 changes the glycosphingolipid homeostasis (3,4,24). To verify the changes in lipid homeostasis in the brain, in particular in the cerebellum, we analyzed the amount of neutral lipids in the cerebellum of P10 (postnatal day 10) and adult WT and GBA2-KO mice by MS, and we distinguished between sphingoid bases (long-chain bases, C18), ceramides (different chain length, saturated and unsaturated), and hexosylceramides (HexCer, different chain length, saturated and unsaturated).…”
Section: Loss Of Gba2 Activity Diminishes Neurite Outgrowthmentioning
confidence: 99%
See 2 more Smart Citations